Bilateral Vestibular Hypofunction: Insights in Etiologies, Clinical Subtypes, and Diagnostics - Lucieer, F.; Vonk, P.; Guinand, N.; Stokroos, R.; Kingma, H.; van de Berg, Raymond (Frontiers in Neurology, 2016)
Objective: To evaluate the different etiologies and clinical subtypes of bilateral vestibular hypofunction (BVH) and the value of diagnostic tools in the diagnostic process of BVH. Materials and methods: A retrospective case review was performed on 154 patients diagnosed with BVH in a tertiary referral center, between 2013 and 2015. Inclusion criteria comprised 1) imbalance and/or oscillopsia during locomotion, and 2) summated slow phase velocity of nystagmus of less than 20 degrees per second during bithermal caloric tests. Results: The definite etiology of BVH was determined in 47% of the cases and the probable etiology in 22%. In 31%, the etiology of BVH remained idiopathic. BVH resulted from more than 20 different etiologies. In the idiopathic group, the percentage of migraine was significantly higher compared to the non-idiopathic group (50% versus 11%, p<0.001). Among all patients, 23.4% were known with autoimmune disorders in their medical history. All 4 clinical subtypes (recurrent vertigo with BVH, rapidly progressive BVH, slowly progressive BVH and slowly progressive BVH with ataxia) were found in this population. Slowly progressive BVH with ataxia comprised only 4.5% of the cases. The head impulse test was abnormal in 94% of the cases. The torsion swing test was abnormal in 66%. Bilateral normal hearing to moderate hearing loss was found in 49%. Blood tests did not often contribute to the determination of the etiology of the disease. Abnormal cerebral imaging was found in 21 patients. Conclusion: BVH is a heterogeneous condition with various etiologies and clinical characteristics. Migraine seems to play a significant role in idiopathic BVH and auto-immunity could be a modulating factor in the development of BVH. The distribution of etiologies of BVH probably depends on the clinical setting. In the diagnostic process of BVH, the routine use of some blood tests can be reconsidered and a low-threshold use of audiometry and cerebral imaging is advised. The torsion swing test is not the “gold standard” for diagnosing BVH due to its lack of sensitivity. Future diagnostic criteria of BVH should consist of standardized vestibular tests combined with a history that is congruent with the vestibular findings.